The Impact of Covid-19 Pandemic: Challenges and Opportunities of Syariah Financial Technology - Ramadhani Irma Tripalupi; Prameshwara Anggahegari (UIN Sunan Gunung Djati Bandung, 2020)
This paper aims to describe the challenges and opportunities of syariah financial technology (fintech) in Indonesia, due to the impact of covid-19 pandemic. Three things that become the focus of writing, include: syariah fintech; the impact of covid-19 pandemic on fintech; syariah fintech opportunities and challenges. This study uses a qualitative approach and descriptive method with documentation/text studies in the form of related data and literature studies. The conclusion of this research is: the growth of Syariah fintech assets at the end of 2019 increased by 2074.81% from the previous year. Although affected by the pandemic, the growth of fintech during this covid-19 pandemic remained relatively stable. Prominent opportunities and challenges for the Syariah fintech resulting from the impact of covid-19 pandemic, including increased use of fintech through online shopping platforms, payments and loans; accelerated digitalization of financial services; slowed economic activity; arose various risks; and decreased debtor/UMKM performance due to the impact of the pandemic.